A Sociocultural Appraisal of Yorùbá Kegites’ Songs - George Olúsolá Ajíbádé (Yoruba Studies Review)
This is a study of how the oral aesthetics of textual production by a group, the Kegites, are used in the construction of an identity rooted in a collective context that reflects a socio-political engagement with the complex social histories of the Yorùbá society and Nigeria at large. The study identifies common practices of the Kegites and themes of the texts of their songs. It shows the practice of engagement by the Kegites through which identity can be textually constructed in ways that politicize self-representation and challenge discourses grounded in the colonial and postcolonial histories of the Yorùbá people. Through the discussion of themes such as ancestral presence, the aesthetics of orature, and the political significance of group or society (ẹgbé) ̣ among the Yorùbá, the paper seeks to showcase the presence of a characteristic of Yorùbá oral literature in which personal, cultural, economic, social and political issues become inseparable. It demonstrates how oral text reflects societal elements and performers use various societal elements to create an expression of an identity within the multiple currents and traditions by taking the rules, creativity, and artistry of self-representation and shaping them with cultural content, as well as with the rhythms and speech patterns of the Yorùbá people.